Building Children's Morals from an Early Age: The Role of The Family in Teaching Apologies, Help, and Gratitude - Loka, Novita; muslimin, Sarmila (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This study aims to describe the role of families in developing children's moral aspects through the habit of saying sorry, please, and thank you at Sayang Bunda Early Childhood Education Center. This study uses a qualitative approach with a case study type of research. The subjects of this study were 17 children and their parents/guardians as well as 4 teachers at Sayang Bunda Early Childhood Education Center with ages ranging from 4 to 6 years old. Data were collected through observation and interviews. The validity of the data obtained was then checked using the triangulation technique involving parents, students, and teachers. Data analysis was conducted using descriptive qualitative methods, consisting of data reduction, data presentation, and conclusion drawing. The results showed that families play an important role in teaching children to say sorry, please, and thank you through role modeling, practice in daily life, and praise or positive reinforcement when children do so. The obstacle faced by parents is the lack of time together due to work commitments, so that practice is mostly done at school. This study provides new insights that synergy between families and schools to optimize the development of children's moral aspects from an early age can be achieved through the habit of saying sorry, please, and thank you.